Upper extremity phlegmasia cerulea dolens complicating supra vena cava embolism in a cervical cancer patient: case report - Ge, Jinting; Weng, Chengxin; Zhao, Jichun; Yuan, Ding; Wang, Tiehao (Frontiers in Cardiovascular Medicine, 2024)
Phlegmasia cerulea dolens (PCD) is a rare yet severe complication of deep vein thrombosis (DVT), characterized by a high amputation rate and mortality. Early diagnosis and treatment are crucial in managing this condition. PCD predominantly affects the lower extremities rather than the upper extremities. We herein present a rare upper extremity PCD case accompanied with supra vena cava and pulmonary embolism in a cervical cancer patient, who presented to our institution with severe pain, edema and irreversible venous gangrene of right upper limb with no response to anticoagulation therapy. Emergency fasciotomy and amputation were performed due to the progressed venous gangrene, however, the patient developed severe infection and coagulation disorders, gastrointestinal bleeding and disseminated intravascular coagulation after the surgery. Despite medical interventions, her family chose to withdraw treatment and the patient died in ICU at the fourth day following emergency surgery.